Combined blockade of thrombin anion binding exosite-1 and PAR4 produces synergistic antiplatelet effect in human platelets - Wu, Chin-Chung; Wang, Wei-Ya; Wei, Chien-Kei; Teng, Che-Ming (Thrombosis and Haemostasis, 2011)
Thrombin exosite-1 mediates the specific binding of thrombin with fibrinogen and protease-activated receptor (PAR) 1. Exosite-1 inhibitors have been shown to effectively decrease the clotting activity of thrombin, while their antiplatelet effects are relatively weak. In the present study, the inhibitory effects of two exosite-1 inhibitors, hirugen and HD1, but not the exosite-2 inhibitor HD22, on thrombin-induced platelet aggregation and P-selectin expression were dramatically enhanced by a PAR4 antagonist, YD-3. In contrast, the PAR1 antagonist SCH-79797 did not affect the antiplatelet effects of exosite-1 inhibitors. The exosite-1 inhibitors and YD-3 prevented the Ca2+ spike and the prolonged Ca2+ response in thrombin-stimulated platelets, respectively; and combination of these two classes of agents led to abolishment of Ca2+ signal. Unlike exosite-1 inhibitors, the antiplatelet effects of the active site inhibitor PPACK and the bivalent inhibitor bivalirudin were not significantly enhanced by YD-3. In addition, the platelet-stimulating activity of γ-thrombin, an autolytic product of α-thrombin which lacks exosite-1, was inhibited by YD-3. These results suggest that the synergistic antiplatelet effects of exosite-1 inhibitor and PAR4 antagonist are resulted from combined blockade of PAR1 and PAR4 in platelets. In fibrinogen or plasma clotting assay, YD-3 neither prolonged the clotting time on its own nor enhanced the anticoagulant activity of exosite-1 inhibitors. Therefore, the combined blockade of exosite-1 and PAR4 may offer a potential strategy for improving the balance of benefits and risks of antithrombotic therapy.
Keywords: Platelet activation; thrombin; exosite; protease-activated receptors